Fabrication of self-standing hyperbranched poly(ethyleneimine) film with shape-memory and copper adsorption behavior via simple polymer reaction with tetraazacalix[2]arene[2]triazine dichloride - Tomohiro Suzuki; Ryota Shibata; Tadashi Tsukamoto; Yuji Shibasaki (Next Materials)
Hyperbranched poly(ethyleneimine) (PEI, Mn 10 kDa) was simply reacted with tetraazacalix[2]arene[2]triazine (ACAT) dichloride in a feed ratio from 1:1 to 1:5 under diluted conditions to produce self-standing PEI modified films with good mechanical strength and thermal properties. In a dynamic mechanical analysis (DMA), the glass transition temperature of the modified polymer was observed from −13.6°C to 35.1 °C, and this value increased with the amount of ACAT modifier. A small relaxation was observed in DMA at temperatures above 70°C, which was due to the partial cleavage of the hydrogen bonds between ACAT and PEI segments. By virtue of these two relaxation phenomena, the PEI modified films exhibited shape-memory properties. Since the films were insoluble in water, their copper adsorption behavior was studied, finding that the modified polymer powder rapidly adsorbed 1.5 mg/g copper ion within 1 h.